Pour une approche constructionnelle de la formation de ‘se V li uns l’autre’. Étude sur corpus - Nkollo, Mikołaj (Studia Romanica Posnaniensia, 2015)
The paper aims to find out which theoretical framework, grammaticalization theory or construction grammar, is better suited to account for mechanisms underlying the emergence of Old French reciprocal string ‘se Verb li uns l’autre’. The data to conduct the analysis have been retrieved from large Latin (Perseus and Vulgate) and Old French (DECT and CoRPTeF) corpora. First, diachronic layers are characterized, encompassing Latin reiterated clusters, late Latin ‘unus alterum’, early French bipartite markers, and the very ‘se Verb li uns l’autre’. Then, their changes are claimed to have come about in response to the evolving system-defining structural properties, as outlined in Natural Morphology. As a result, instead of being couched in terms of more / less grammatical, the reconstruction of how particular reciprocal structures came into being is more felicitous if they are treated as full-fledged form-meaning pairs. Indeed, they exhibit significant variation along two clines: schematic – substantive and complex - atomic. As for further stages of its evolution, ‘se Verb li uns l’autre’ is shown to have become different from its forerunners in that it had reached a discursively more subjective status.